2011
DOI: 10.3892/ol.2011.504
|View full text |Cite
|
Sign up to set email alerts
|

MLH1-deficient HCT116 colon tumor cells exhibit resistance to the cytostatic and cytotoxic effect of the poly(A) polymerase inhibitor cordycepin (3′-deoxyadenosine) in vitro

Abstract: Abstract. Cordycepin (3'-deoxyadenosine) is an inhibitor of poly(A) polymerase (PAP), an enzyme crucial to mRNA 3'-end processing, which produces the shortening of poly(A) tails, leading to the destabilization of mRNAs. Cordycepin inhibits proliferation and induces apoptosis in tumor cells, indicating its antitumor activity. Defective 3'-end processing is associated with hypersensitivity to UV treatment. We investigated the effects of cordycepin on proliferation and apoptosis in MLH1-deficient and MLH1-profici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…[42][43][44][45][46] Using these approaches, we analyzed the consequences of VUS function in CRC cell line models in which no wt copy of each affected gene was present. We transfected plasmids expressing the MSH2 series VUS into LoVo cells, 47 the MLH1 series into HCT116 cells, 48 and the PMS2 series into Vaco481 cells 49 (Fig S2 and S3). In the absence of endogenous wt forms of each protein, the protein expression patterns for each VUS were generally similar to those observed in the HEK293 cells (Fig.…”
Section: Impact Of Mmr Vus On Basal Cellular Viabilitymentioning
confidence: 99%
“…[42][43][44][45][46] Using these approaches, we analyzed the consequences of VUS function in CRC cell line models in which no wt copy of each affected gene was present. We transfected plasmids expressing the MSH2 series VUS into LoVo cells, 47 the MLH1 series into HCT116 cells, 48 and the PMS2 series into Vaco481 cells 49 (Fig S2 and S3). In the absence of endogenous wt forms of each protein, the protein expression patterns for each VUS were generally similar to those observed in the HEK293 cells (Fig.…”
Section: Impact Of Mmr Vus On Basal Cellular Viabilitymentioning
confidence: 99%
“…Also they noted that cells with defective MMR function showed resistance to certain anticancer drugs. So Imesch et al [6] found that MLH1-deficient tumor cells exhibited reduced susceptibility to apoptosis upon treatment with cordycepin, as compared to MLH1-proficient tumor cells.…”
Section: Reviews Of Mechanisms Resistance To the Cytostatic And Cytotmentioning
confidence: 99%
“…Describing mechanism of Cordycepin (3'-deoxyadenosine) cytotoxic effect, Imesch et al [6] researched Cordycepin cytotoxic effect studying both transcription processes, as an inhibitor of Poly (A) Polymerase (PAP), and DNA replication, as MLH1-one of the five DNA Mismatch Repair (MMR) proteins, i.e., processes involved in G2/M phases of cellular cycle. Also they noted that cells with defective MMR function showed resistance to certain anticancer drugs.…”
Section: Reviews Of Mechanisms Resistance To the Cytostatic And Cytotmentioning
confidence: 99%
“…Also they noted that cells with defective MMR function showed resistance to certain anticancer drugs. So Imesch P, et al [25] found that MLH1-deficient tumor cells exhibited reduced susceptibility to apoptosis upon treatment with cordycepin, as compared to MLH1-proficient tumor cells.…”
Section: Mechanism Of Cordycepin (3'-deoxyadenosine) Cytotoxic Effectmentioning
confidence: 99%
“…Describing mechanism of cordycepin (3'-deoxyadenosine) cytotoxic effect, Imesch P, et al [25] found that cordycepin cytotoxic effect via study both transcription processes as an inhibitor of poly(A) polymerase (PAP) and DNA replication focused on MLH1 [one of the five DNA mismatch repair (MMR) proteins], i.e. processes which operate in G2/M phases of cellular cycle.…”
Section: Mechanism Of Cordycepin (3'-deoxyadenosine) Cytotoxic Effectmentioning
confidence: 99%